2018
DOI: 10.1002/sdtp.12554
|View full text |Cite
|
Sign up to set email alerts
|

26‐2: Extremely High‐Efficient OLED Achieving External Quantum Efficiency over 40% by Carrier Injection Layer with Super‐Low Refractive Index

Abstract: Extremely low-refractive-index hole-injection and electroninjection layers were developed to improve the outcoupling efficiency of an organic light-emitting diode (OLED). These layers enabled a remarkably high external quantum efficiency of 41% in a bottom-emission phosphorescent OLED and also improved the current efficiency even in a top-emission OLED with a microcavity structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Combining the fact that the PL lifetimes of the MAPbBr 3 film and the MAPbBr 3 /Bphen film are nearly identical (see Figure S5, Supporting Information), it is possible that the Bphen layer only affects the light out‐coupling of perovskites rather than the carrier dynamics. Since PTAA shares a similar refractive index (≈1.7) as Bphen, [ 24,25 ] similar light out‐coupling effects that reduce the gain property (SE intensity) can be expected. Thus, the light out‐coupling effect of the transport layers is also excluded to explain the simultaneously enhanced ASE emission and suppressed spontaneous emission after combining an additional PTAA layer.…”
Section: Resultsmentioning
confidence: 99%
“…Combining the fact that the PL lifetimes of the MAPbBr 3 film and the MAPbBr 3 /Bphen film are nearly identical (see Figure S5, Supporting Information), it is possible that the Bphen layer only affects the light out‐coupling of perovskites rather than the carrier dynamics. Since PTAA shares a similar refractive index (≈1.7) as Bphen, [ 24,25 ] similar light out‐coupling effects that reduce the gain property (SE intensity) can be expected. Thus, the light out‐coupling effect of the transport layers is also excluded to explain the simultaneously enhanced ASE emission and suppressed spontaneous emission after combining an additional PTAA layer.…”
Section: Resultsmentioning
confidence: 99%
“…In the work reported by Watabe et al,68 a remarkably high EQE of 41.0% was demonstrated in a bottom‐emission PhOLED by combining HIL and EIL, both of which exhibit super low refractive indices. This is in a strong contrast with the fact that a reference control device containing conventional HIL and EIL yielded an EQE of 30.5%.…”
Section: Toward the Ultimate Limit Of The Optical Efficiency In Oledsmentioning
confidence: 88%
“…They showed that they could reduce the RI of the tris(8-hydroxyquinoline)aluminum (Alq 3 )-based ETL from 1.75 to 1.45, and consequently increase the outcoupling by 30%. Independently, Watabe et al [57] developed hole and electron injection layer (HIL and EIL, respectively) materials, based on blends of a metal oxide such as MoO x and an organic compound, with RIs <1.6 and <1.5, respectively. As a result, their OLED EQEs increased from 30% to 41%.…”
Section: Manipulating the Refractive Index Of The Organic Layersmentioning
confidence: 99%